Photocatalyst, preparation method and application thereof
By synthesizing a modified photocatalyst POSS-PDI and combining it with g-CN to form a heterojunction photocatalyst, the problem of low efficiency in the depolymerization of lignin C-C bonds was solved, achieving high conversion rate and selectivity, and simplifying the synthesis process.
Patent Information
- Application Number
- CN202310603643.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2043-05-25
AI Technical Summary
Existing technologies struggle to efficiently depolymerize lignin C-C bonds under mild conditions, and traditional catalytic methods require expensive chemical oxidants and harsh reaction conditions, resulting in poor yields and selectivity.
By synthesizing the modified photocatalyst POSS-PDI and combining it with the g-CN photocatalyst, a type II n-h heterojunction photocatalyst was formed, which utilized its band structure advantage to improve the recombination rate of photogenerated carriers.
The conversion rate of lignin model material exceeded 99%, and the C-C bond depolymerization selectivity reached 96%, which simplified the synthesis process and expanded the application range of photocatalysts.
Smart Images

Figure CN116726986B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical energy, specifically to a photocatalyst, its preparation method, and its application. Background Technology
[0002] With the increasing cost of fossil-derived resources and their limited supply, the development of technologies for producing commercial chemicals and fuels from renewable raw materials has become a focus of attention in the field of green chemistry. As a 15-25% component of natural lignocellulose, lignin can serve as a substitute for fossil resources in the production of aromatic raw materials chemicals. In different bonding models of natural lignin, the breaking of the C-C bond in β-aryl ethers (β-O-4 model) is considered a key step in lignin depolymerization, making selective C-C depolymerization a significant but challenging problem.
[0003] However, using conventional methods to depolymerize and separate the C-C bonds in the β-O-4 model is impractical. Most reported catalytic methods require expensive, toxic chemical oxidants and energy-intensive, harsh reaction conditions, and their yields and selectivity are unsatisfactory.
[0004] Currently, photocatalytic redox under mild conditions is an effective and promising method for lignin depolymerization, stably yielding aromatic aldehydes (or acids), esters, and other products. However, most monomer photocatalysts require harsh light conditions and lengthy reaction times, and the separation of the reactive species—electron-hole pairs—is difficult, resulting in depolymerization performance still falling short of expectations. To address these issues, one of the most comprehensive strategies is to construct heterojunctions between high-performing monomer photocatalysts and other materials (such as transition metal sulfides, transition metal oxides, metal complexes, and metal-organic frameworks). Therefore, the search for two structurally suitable and synergistically mechanistic photocatalysts to construct heterojunctions has become a growing trend. Summary of the Invention
[0005] To address the shortcomings and deficiencies in the research on the depolymerization of lignin by monomer photocatalysts, this invention provides a photocatalyst and its preparation method. By synthesizing the modified photocatalyst POSS-PDI and using a simple method to combine it with the g-CN photocatalyst, the high recombination rate of photogenerated carriers in the monomer photocatalyst is improved by leveraging the band advantage of the type II n-h heterojunction photocatalyst. The prepared photocatalyst achieves a lignin model material conversion rate of over 99% and a C-C bond depolymerization selectivity of 96%.
[0006] To solve the above problems, the technical solution adopted by the present invention is as follows:
[0007] A photocatalyst is a modified photocatalyst POSS-PDI; the modified photocatalyst POSS-PDI is a CPDI photocatalyst with cage-like groups POSS-NH2 added; the mass ratio of CPDI photocatalyst to cage-like groups POSS-NH2 is 1:3.29.
[0008] Optionally, a modified photocatalyst, POSS-PDI, is prepared by imidazole reaction of 3,4,9,10-perylenetetracarboxylic dianhydride, POSS-NH2, and imidazole.
[0009] Optionally, the modified photocatalyst POSS-PDI is obtained by imidazole reaction, specifically comprising: 2.0 g of 3,4,9,10-perylenetetracarboxylic dianhydride, 6.58 g of POSS-NH2 and 20 g of imidazole, purged with N2 for 15 min, 4 mL of o-dichlorobenzene is added, and the mixture is stirred vigorously at 125 °C for 5 h; the mixture is cooled to 90 °C, 60 mL of methanol is added, filtered and separated, and further purified by silica gel column chromatography using a CHCl3 / acetone eluent with a volume ratio of 20 / 1.
[0010] A photocatalyst is a type II photocatalyst formed by combining g-CN and a modified photocatalyst POSS-PDI; wherein the modified photocatalyst POSS-PDI is a CPDI photocatalyst with cage-like groups POSS-NH2 added, and the mass ratio of CPDI photocatalyst to cage-like groups POSS-NH2 is 1:3.29; wherein the mass ratio of g-CN to modified photocatalyst POSS-PDI in the type II photocatalyst is 3wt%.
[0011] Optionally, a modified photocatalyst POSS-PDI is prepared by imidazole reaction of 3,4,9,10-perylenetetracarboxylic dianhydride, POSS-NH2 and imidazole; then g-CN and the modified photocatalyst POSS-PDI are placed in a mixed solvent and allowed to stand to form a type II photocatalyst.
[0012] Optionally, the modified photocatalyst POSS-PDI is obtained via imidazoleization reaction, specifically comprising: 2.0 g of 3,4,9,10-perylenetetracarboxylic dianhydride, 6.58 g of POSS-NH2 and 20 g of imidazole, purged with N2 for 15 min, 4 mL of o-dichlorobenzene added, and vigorously stirred at 125 °C for 5 h; the mixture is cooled to 90 °C, 60 mL of methanol is added, filtered and separated, and further purified by silica gel column chromatography using a CHCl3 / acetone eluent at a volume ratio of 20 / 1.
[0013] Optionally, the mixed solvent is carbon tetrachloride and methanol added sequentially; the volume ratio of carbon tetrachloride to methanol in the mixed solvent is 1:30, and the standing time is 1 hour.
[0014] Optionally, g-CN can be prepared by a two-step chemical exfoliation method, specifically including: heating melamine powder to 550°C at 2.3°C / min and holding for 4 hours to obtain g-CN blocks; heating g-CN block powder to 520°C at 5°C / min and holding for 5 hours to obtain g-CN.
[0015] The photocatalyst described in this invention is used for the depolymerization of lignin model compound β-O-4.
[0016] Optionally, in acetonitrile solvent, the mass ratio of the lignin model compound β-O-4 to the photocatalyst is 1.2 / 10; the catalytic reaction conditions are: light irradiation, 6℃ and oxygen atmosphere; the light irradiation conditions are: xenon lamp, 300W, full spectrum; the stirring speed is: 500r / min.
[0017] The present invention has the following beneficial effects:
[0018] 1) This invention solves the problem of high crystallinity and easy agglomeration of CPDI photocatalyst by incorporating cage-like groups POSS-NH2.
[0019] 2) This invention prepares a type II heterojunction photocatalyst by combining POSS-PDI and g-CN, which enhances the π-π conjugation effect and broad spectral response at the interface, forms an interleaved band structure, and achieves excellent charge carrier mobility.
[0020] 3) The synthesis method of this invention is simple and not limited to the synthesis of a single photocatalyst. It can be extended to the synthesis and design of photocatalysts with similar group types or band structures. Attached Figure Description
[0021] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:
[0022] Figure 1 Images showing the changes in the depolymerization effect of lignin on the CPDI and POSS-PDI photocatalysts prepared in Example 1;
[0023] Figure 2 The images show the changes in the CPDI and POSS-PDI photocatalysts prepared in Example 1. (a) and (b) represent the scanning electron microscope images of CPDI and POSS-PDI, respectively.
[0024] Figure 3 The image shows a transmission electron microscope (TEM) image of the POSS-PDI photocatalyst prepared in Example 1.
[0025] Figure 4Images showing the changes in the depolymerization effect of g-CN, POSS-PDI, and photocatalysts prepared in Examples 2-7;
[0026] Figure 5 The images are scanning electron microscope (SEM) images of the photocatalysts prepared in Examples 3-7, where (a)-(e) represent the SEM images of the photocatalysts prepared in Examples 3-7, respectively.
[0027] Figure 6 Transmission electron microscopy images of g-CN and photocatalysts prepared in Examples 2 and 5;
[0028] Figure 7 The energy dispersive spectrum of the photocatalyst prepared in Example 5 is shown below.
[0029] Figure 8 The X-ray diffraction patterns of the photocatalysts prepared in Examples 2-7 are shown below.
[0030] Figure 9 Images showing the changes in the depolymerization effect of lignin in the materials obtained under different reaction conditions in Examples 9-13;
[0031] Figure 10 Images showing the changes in the depolymerization effect of lignin in the materials obtained at different reaction times in Examples 14-19;
[0032] Figure 11 The UV-Vis absorption spectra (a), time-resolved fluorescence decay spectra (b), transient photocurrent (c), and electrochemical impedance images (d) of g-CN, POSS-PDI, g-CN / CPDI, and the photocatalyst are shown. Detailed Implementation
[0033] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] I. Explanation of Abbreviations:
[0035] CPDI: 3,4,9,10-Perylenetetracarboxylic acid dianhydride;
[0036] POSS-NH2: Aminopropylheptyl-cage polysilsesquioxane;
[0037] g-CN: Mesoporous graphitic carbon nitride nanosheets;
[0038] The photocatalyst of the present invention is a modified photocatalyst POSS-PDI; the modified photocatalyst POSS-PDI is a CPDI photocatalyst with cage-like groups POSS-NH2 added; the mass ratio of CPDI photocatalyst to cage-like groups POSS-NH2 is 1:3.29.
[0039] In the embodiments of this disclosure, a modified photocatalyst POSS-PDI was prepared by imidazole reaction of 3,4,9,10-perylenetetracarboxylic dianhydride, POSS-NH2, and imidazole.
[0040] In the embodiments of this disclosure, the modified photocatalyst POSS-PDI was obtained by imidazole reaction, specifically comprising: 2.0 g of 3,4,9,10-perylenetetracarboxylic acid dianhydride, 6.58 g of POSS-NH2 and 20 g of imidazole mixed together, purged with N2 for 15 min, 4 mL of o-dichlorobenzene added, and stirred vigorously at 125 °C for 5 h; the mixture was cooled to 90 °C, 60 mL of methanol was added, filtered and separated, and further purified by silica gel column chromatography using a CHCl3 / acetone eluent with a volume ratio of 20 / 1.
[0041] Furthermore, the photocatalyst of the present invention is a type II photocatalyst formed by combining g-CN and modified photocatalyst POSS-PDI; the modified photocatalyst POSS-PDI is a CPDI photocatalyst with cage-like groups POSS-NH2 added, and the mass ratio of CPDI photocatalyst to cage-like groups POSS-NH2 is 1:3.29; the mass ratio of g-CN to modified photocatalyst POSS-PDI in the type II photocatalyst is 3wt%.
[0042] In the embodiments of this disclosure, a modified photocatalyst POSS-PDI was prepared by imidazole reaction of 3,4,9,10-perylenetetracarboxylic dianhydride, POSS-NH2 and imidazole; g-CN and the modified photocatalyst POSS-PDI were then placed in a mixed solvent and allowed to stand to form a type II photocatalyst.
[0043] In the embodiments of this disclosure, the modified photocatalyst POSS-PDI was obtained by imidazole reaction, specifically comprising: 2.0 g of 3,4,9,10-perylenetetracarboxylic dianhydride, 6.58 g of POSS-NH2 and 20 g of imidazole mixed together, purged with N2 for 15 min, 4 mL of o-dichlorobenzene added, and stirred vigorously at 125 °C for 5 h; the mixture was cooled to 90 °C, 60 mL of methanol was added, filtered and separated, and further purified by silica gel column chromatography using a CHCl3 / acetone eluent with a volume ratio of 20 / 1 to obtain the final product;
[0044] In the embodiments of this disclosure, the mixed solvent is carbon tetrachloride and methanol added sequentially; the volume ratio of carbon tetrachloride to methanol in the mixed solvent is 1:30, and the standing time is 1 hour.
[0045] In the embodiments of this disclosure, g-CN is prepared by a two-step chemical exfoliation method, specifically including: heating melamine powder to 550°C at 2.3°C / min and holding for 4 hours to obtain g-CN blocks; heating g-CN block powder to 520°C at 5°C / min and holding for 5 hours to obtain the final product.
[0046] The photocatalyst of the present invention is used for the depolymerization of lignin model compound β-O-4.
[0047] In the embodiments of this disclosure, the mass ratio of the lignin model compound β-O-4 to the photocatalyst in the acetonitrile solvent is 1.2 / 10; the catalytic reaction conditions are: light irradiation, 6°C and oxygen atmosphere; the light irradiation conditions are: xenon lamp, 300W, full spectrum; the stirring speed is: 500r / min.
[0048] The photocatalyst of the present invention is prepared by first preparing a modified photocatalyst POSS-PDI, which can be prepared by imidazole reaction using commercially available 3,4,9,10-perylenetetracarboxylic dianhydride, POSS-NH2 and imidazole; g-CN can be prepared by a two-step chemical exfoliation method using melamine powder; and POSS-PDI and g-CN are combined by solvent evaporation deposition to obtain the photocatalyst.
[0049] Experimental results show that the mass ratio of CPDI to POSS-NH2 in the modified photocatalyst is 1:3.29, and the mass ratio of g-CN to POSS-PDI in the type II photocatalyst is 3wt%. Under the above raw material ratios, the g-CN / P-PDI type II heterojunction photocatalyst has a better depolymerization effect on the lignin model compound β-O-4. At the same time, it is demonstrated that by incorporating the cage-like group POSS-NH2, the present invention forms a POSS-PDI photocatalyst, which solves the problem of high crystallinity and easy agglomeration of CPDI photocatalyst, enhances the π-π conjugation effect and broad spectral response of the interface, forms an interlaced band structure, and achieves excellent charge carrier mobility.
[0050] Specifically, it includes:
[0051] Preparation of mesoporous graphitic carbon nitride nanosheets g-CN: 10 g of melamine powder was placed in a covered alumina crucible and heated to 550 °C in a muffle furnace at a rate of 2.3 °C / min, and held for 4 h. After cooling to room temperature, g-CN nanoparticles were obtained. Alternatively, after grinding in an agate mortar, 10 g of g-CN nanoparticle powder was placed in a covered alumina crucible and heated to 520 °C in a muffle furnace at a rate of 5 °C / min, and held for 5 h. After cooling to room temperature, g-CN nanosheets were obtained.
[0052] Preparation of POSS-PDI: 3,4,9,10-perylenetetracarboxylic dianhydride (PDI, 2.0 g, 2.89 mmol), aminopropylheptyl-cage polysilsesquioxane (POSS-NH2, 6.58 g, 7.52 mmol), and 20 g imidazole were added to a flask. The mixture was purged with a stream of N2 for 15 min. Then, 4 mL of o-dichlorobenzene was added, and the mixture was heated to 125 °C and stirred vigorously for 5 h. The mixture was cooled to 90 °C, 60 mL of methanol was added, and the mixture was filtered and separated. Further purification was performed by silica gel column chromatography using 20 / 1 (v / v) CHCl3 / acetone as eluent, followed by vacuum drying at 60 °C for 12 h.
[0053] Preparation of g-CN / POSS-PDI: Dissolve 0.01 g POSS-PDI in 1 mL of CCl4 (a good solvent) and add 2 g g-CN. Add 30 mL of methanol (a poor solvent) to the above solution at once; a pink, insoluble solid precipitate immediately appears. Let stand for 1 h. Centrifuge the sample, wash three times with methanol, and dry in vacuum at 60 °C for 12 h. Based on this, g-CN / POSS-PDI with different mass ratios (0.5 wt%, 1 wt%, 3 wt%, 5 wt%, and 7 wt%) were prepared, denoted as g-CN / P-PDI-0.5, g-CN / P-PDI-1, g-CN / P-PDI-3, g-CN / P-PDI-5, and g-CN / P-PDI-7, respectively.
[0054] The g-CN / POSS-PDI photocatalyst described in this invention was used for the depolymerization of 1 mg / mL lignin β-O-4 model compound. Under the conditions of illumination (xenon lamp, 300W, full spectrum), stirring (500 r / min), constant temperature (6℃), acetonitrile solvent, and oxygen atmosphere, the reaction time was 3 h, resulting in a lignin model compound conversion rate of over 99% and a C-C bond depolymerization selectivity of 96%.
[0055] The present invention will be further illustrated below with detailed structures and examples of specific embodiments. However, the present invention is not limited to the following embodiments. Any variations are included within the technical scope of the present invention without departing from the spirit described above.
[0056] Example 1:
[0057] The modified photocatalyst POSS-PDI was prepared as follows: 3,4,9,10-perylenetetracarboxylic dianhydride (PDI, 2.0 g, 2.89 mmol), aminopropylheptyl-cage polysilsesquioxane (POSS-NH2, 6.58 g, 7.52 mmol), and 20 g imidazole were added to a flask. The mixture was purged with N2 gas for 15 min. Then, 4 mL of o-dichlorobenzene was added, and the mixture was heated to 125 °C and stirred vigorously for 5 h. The mixture was cooled to 90 °C, 60 mL of methanol was added, and the mixture was filtered and separated. Further purification was performed by silica gel column chromatography using 20 / 1 (v / v) CHCl3 / acetone as eluent. The mixture was then dried under vacuum at 60 °C for 12 h and used for the depolymerization of lignin β-O-4 model compounds.
[0058] The comparison of the depolymerization effect of the materials prepared in Example 1, their scanning electron microscope (SEM) images, and the transmission electron microscope (TEM) images of the modified photocatalyst POSS-PDI are shown below. Figure 1-3 As shown. By Figure 1 It can be seen that, under constant conditions, the modified catalyst POSS-PDI exhibits superior performance in terms of conversion, yield, and CC cleavage selectivity for depolymerizing lignin model compounds. Figure 2-3 It is evident that the incorporation of the cage-like group POSS-NH2 alters the agglomeration and crystallization of the photocatalyst. The CPDI catalyst exhibits small cylindrical structures with tight aggregation, while the modified POSS-PDI catalyst is more dispersed, resembling plates. Furthermore, transmission electron microscopy (TEM) characterization of the modified POSS-PDI catalyst also revealed the presence of these plates, indicating the successful preparation of the modified catalyst.
[0059] Example 2:
[0060] The g-CN photocatalyst was prepared as follows: 10 g of melamine powder was placed in a covered alumina crucible and heated to 550 °C in a muffle furnace at a rate of 2.3 °C / min, and held for 4 h. After cooling to room temperature, g-CN nanoparticles were obtained. After grinding in an agate mortar, 10 g of g-CN nanoparticle powder was placed in a covered alumina crucible and heated to 520 °C in a muffle furnace at a rate of 5 °C / min, and held for 5 h. After cooling to room temperature, g-CN was obtained and used for the depolymerization of lignin β-O-4 model compounds.
[0061] Example 3:
[0062] The photocatalyst was prepared as follows: 0.01 g POSS-PDI was dissolved in 1 mL CCl4 (a good solvent), and 2 g g-CN was added. 30 mL of methanol (a poor solvent) was added to the solution at once, and a pink, insoluble solid precipitate immediately appeared. The mixture was allowed to stand for 1 h. The sample was centrifuged, washed three times with methanol, and dried under vacuum at 60 °C for 12 h. The resulting mass ratio (m...) was... POSS-PDI:m g-CN ) is a 0.5 wt% photocatalyst, simplified as g-CN / P-PDI-0.5, and is used for the depolymerization of lignin β-O-4 model.
[0063] Example 4:
[0064] The difference between this embodiment and Example 3 is that the amount of POSS-PDI and g-CN added is 0.02g and 2g, respectively, and the mass ratio of photocatalyst is 1wt%, which is simplified as g-CN / P-PDI-1.
[0065] Example 5:
[0066] The difference between this embodiment and Example 3 is that the amount of POSS-PDI and g-CN added is 0.06g and 2g, respectively, and the mass ratio of photocatalyst is 3wt%, which is simplified as g-CN / P-PDI-3.
[0067] Example 6:
[0068] The difference between this embodiment and embodiment 3 is that the amount of POSS-PDI and g-CN added is 0.10g and 2g, respectively, and the mass ratio of photocatalyst is 5wt%, which is simplified as g-CN / P-PDI-5.
[0069] Example 7:
[0070] The difference between this embodiment and Example 3 is that the amount of POSS-PDI and g-CN added is 0.14g and 2g, respectively, and the mass ratio of photocatalyst is 7wt%, which is simplified as g-CN / P-PDI-7.
[0071] Example 8:
[0072] The difference between this embodiment and Embodiment 3 is that the added samples are CPDI and g-CN, and the mass ratio (m) is obtained. CPDI :m g-CN (3wt% of the photocatalyst, simplified as g-CN / CPDI-3, was used for the depolymerization of lignin β-O-4 model compounds.)
[0073] For a comparison of the depolymerization effects of the materials prepared in Examples 2-8, and detailed images including scanning electron microscope (SEM), transmission electron microscope (TEM), energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD) spectra, please refer to [link to examples]. Figure 4-8 .
[0074] Depend on Figure 4 It can be seen that, under constant conditions, changing the mass ratio of the photocatalyst results in different depolymerization effects on the lignin model compound. The depolymerization effect of the photocatalyst is optimal when the mass ratio of POSS-PDI to g-CN is 3wt%.
[0075] Illustration from scanning electron microscope Figure 5 It can be seen that, under constant conditions, changing the mass ratio of the photocatalyst results in different morphologies of the final photocatalyst. As the loading of POSS-PDI increases, the embedded rod-shaped supports formed on the g-CN surface gradually become denser. Figure 5 a and Figure 5 The photocatalyst b failed to completely cover the surface of g-CN due to the low loading of POSS-PDI. Figure 5 In c, the loading of POSS-PDI is 3wt% of the mass of g-CN, basically covering the surface of g-CN. Figure 5 d and Figure 5 The photocatalyst for e exhibits a certain degree of accumulation on the g-CN surface due to its high POSS-PDI loading. Therefore, when the mass ratio of POSS-PDI to g-CN is 3wt%, the photocatalyst is successfully prepared, and its morphology and structure best meet the catalytic requirements.
[0076] Images from scanning electron microscopy and transmission electron microscopy. Figure 6 The microstructure of the photocatalysts is revealed; the g-CN and POSS-PDI samples exhibit typical stacked sheet-like structures. The amorphous morphology of POSS-PDI is also observed, forming a uniformly distributed smooth film on the g-CN surface. Energy dispersive spectroscopy is also shown. Figure 7 This indicates the presence of C, N, O, and Si atoms in the photocatalyst, proving that POSS-PDI is uniformly distributed on the exposed g-CN surface and that there are no impurity elements.
[0077] X-ray diffraction diagram Figure 8 As can be seen, the g-CN sample exhibits two typical peaks at 13.1° and 27.5°, which originate from the (100) in-plane sequence of the triazine segments and the (002) interlayer stacking of the conjugated graphitic components. PDI shows several diffraction peaks at 12.0° and 25.0°, corresponding to the (020) and (020) planes, respectively. After coupling different contents of POSS-PDI with g-CN ( Figure 8 (b) All photocatalysts retained the typical peaks of graphitic carbon nitride at 2θ = 13.1° and 27.5°, indicating the structural integrity of g-CN. Furthermore, a peak belonging to POSS-PDI was observed at 8.4°, but its intensity was much weaker than that of pure POSS-PDI. This suggests that due to the adsorption of POSS-PDI molecules on the g-CN surface, the molecular arrangement in the photocatalysts is less ordered than that in the original POSS-PDI, as evidenced by the scanning electron microscopy and transmission electron microscopy results described above.
[0078] Example 9:
[0079] The depolymerization reaction conditions of lignin model compound β-O-4 are as follows: 10 mg of the prepared photocatalyst was weighed and placed in a reaction vessel containing 5 mL of model compound β-O-4 (1.2 mg / mL) and stirred (500 r / min). The reaction was carried out under light irradiation (xenon lamp, 300 W, full spectrum) at 6 °C in an acetonitrile solvent and oxygen atmosphere for 3 h.
[0080] Example 10:
[0081] The difference between this embodiment and Embodiment 9 is that the catalytic reaction is carried out under the influence of no light source.
[0082] Example 11:
[0083] The difference between this embodiment and Embodiment 9 is that the catalytic reaction is carried out in a helium atmosphere.
[0084] Example 12:
[0085] The difference between this embodiment and Example 9 is that the catalytic reaction is carried out in ethanol solvent.
[0086] Example 13:
[0087] The difference between this embodiment and Example 9 is that the catalytic reaction is carried out in tetrahydrofuran solvent.
[0088] The depolymerization effects of Examples 9-13 are compared in sequence. Figure 9 It can be seen that changing the conditions of the depolymerization reaction has different effects on the results. A light source is the first condition for the reaction to proceed, and an oxygen atmosphere that promotes the oxidation reaction is also necessary. Changing the type of solvent will also affect the reaction to varying degrees. Therefore, it can be concluded that Example 9 represents the most suitable catalytic conditions for the reaction to proceed.
[0089] Example 14:
[0090] The depolymerization reaction conditions of lignin model compound β-O-4 are as follows: 10 mg of the prepared photocatalyst is weighed and placed in a reaction vessel containing 5 mL of model compound β-O-4 (1.2 mg / mL) and stirred (500 r / min). The reaction is carried out under light irradiation (xenon lamp, 300 W, full spectrum) at 6 °C in an acetonitrile solvent and oxygen atmosphere for 0.5 h.
[0091] Example 15:
[0092] The difference between this embodiment and Example 14 is that the catalytic reaction time is 1 hour.
[0093] Example 16:
[0094] The difference between this embodiment and Example 14 is that the catalytic reaction time is 1.5 hours.
[0095] Example 17:
[0096] The difference between this embodiment and Example 14 is that the catalytic reaction time is 2 hours.
[0097] Example 18:
[0098] The difference between this embodiment and Example 14 is that the catalytic reaction time is 2.5 hours.
[0099] Example 19:
[0100] The difference between this embodiment and Example 14 is that the catalytic reaction time is 3 hours.
[0101] The depolymerization effects of Examples 14-19 are compared in sequence. Figure 10 It can be seen that, under constant conditions, the yield of the depolymerization reaction tends to the theoretical limit as time increases. When the reaction time is 3 hours, the conversion rate of the lignin model compound β-O-4 reaches 99%, and the yield reaches its maximum. Therefore, the optimal reaction time is 3 hours.
[0102] At the same time, such as Figure 11 As shown, charge transfer kinetics were investigated using photoelectrochemical experiments and steady-state and transient fluorescence spectroscopy to further explore the influence of heterojunction structure on the enhancement of photocatalytic oxidation activity. Figure 11 As shown in Figure a, the UV-Vis absorption spectra of these catalysts were investigated. The g-CN nanosheets exhibited a visible absorption edge near 460 nm, while POSS-PDI and CPDI showed very broad absorption in the UV-NIR region. When POSS-PDI and CPDI formed heterojunctions with g-CN, significant absorption peaks appeared in the 450-650 nm range, in addition to the main absorption of g-CN. DRS results indicate that, compared to g-CN, the heterostructured photocatalysts exhibit stronger light-harvesting capabilities. Figure 11 As shown in b, time-resolved fluorescence decay curves were measured at a collection wavelength of 375 nm, and a triple exponential function was fitted. The calculated mean radiative lifetimes (τave) of g-CN, POSS-PDI, and the photocatalyst were 1.43, 1.90, and 0.73 ns, respectively. The quenched PL intensity and accelerated PL decay indicate that the recombination probability of photogenerated electron-hole pairs has been significantly reduced. The transient photocurrent responses of different samples are shown in Figure b. Figure 11 As shown in c, the transient photocurrents of all samples were very stable during cycling. CPDI and POSS-PDI showed weak photocurrent responses, while g-CN had a slightly higher response. The photocurrent response of the photocatalyst was approximately 4.8 times that of g-CN, 170 times that of POSS-PDI, and 1.5 times that of g-CN / CPDI-3, indicating that the photocurrent response of the photocatalyst after loading POSS-PDI was significantly higher. - -h + The separation of pairs was significantly improved. Figure 11 Figure d shows the EIS Nyquist plots for different samples. It can be observed that the arc radius of POSS-PDI is smaller than that of CPDI. Furthermore, the composition of the POSS-PDI and g-CN heterojunction significantly reduces the arc radius of g-CN, indicating that it more effectively separates photogenerated electrons and holes. Loading POSS-PDI onto g-CN minimizes the resistance to carrier transfer, which is beneficial for surface charge transfer.
[0103] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0104] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
[0105] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.
Claims
1. A photocatalyst, characterized in that, It is a type II photocatalyst formed by combining g-CN with the modified photocatalyst POSS-PDI; The modified photocatalyst POSS-PDI is a CPDI photocatalyst with cage-like groups POSS-NH2 added, and the mass ratio of CPDI photocatalyst to cage-like groups POSS-NH2 is 1:3.29; the mass ratio of g-CN to modified photocatalyst POSS-PDI in the type II photocatalyst is 3wt%. A modified photocatalyst, POSS-PDI, was prepared by imidazole reaction of 3,4,9,10-perylenetetracarboxylic dianhydride, POSS-NH2, and imidazole. Specifically, the mixture consisted of 2.0 g of 3,4,9,10-perylenetetracarboxylic dianhydride, 6.58 g of POSS-NH2, and 20 g of imidazole. The mixture was purged with N2 for 15 min, and 4 mL of o-dichlorobenzene was added. The mixture was stirred vigorously at 125 °C for 5 h. The mixture was cooled to 90 °C, 60 mL of methanol was added, and the mixture was filtered. Further purification was achieved by silica gel column chromatography using a 20 / 1 (v / v) CHCl3 / acetone solution. g-CN was prepared by a two-step chemical exfoliation method, specifically including: heating melamine powder to 550°C at 2.3°C / min and holding for 4 hours to obtain g-CN blocks; and heating the g-CN block powder to 520°C at 5°C / min and holding for 5 hours to obtain g-CN. Then, g-CN and the modified photocatalyst POSS-PDI were placed in a mixed solvent and allowed to stand to form a type II photocatalyst.
2. The photocatalyst according to claim 1, characterized in that, The mixed solvent is carbon tetrachloride and methanol added sequentially; The volume ratio of carbon tetrachloride to methanol in the mixed solvent is 1:30, and the standing time is 1 hour.
3. The application of the photocatalyst according to claim 1 or 2 for the depolymerization of lignin model compound β-O-4; In acetonitrile solvent, the mass ratio of the lignin model compound β-O-4 to the photocatalyst was 1.2 / 10; the catalytic reaction conditions were: light irradiation, 6℃ and oxygen atmosphere; the light irradiation conditions were: xenon lamp, 300W, full spectrum; the stirring speed was 500r / min.
Citation Information
Patent Citations
Preparation method and application of PDI functionalized 3D g-C3N4 photocatalyst
CN115178294A
Novel polyhedral oligomeric silsesquioxane (POSS) based fluorescent colorants
US20080029739A1